THE EFFECT OF BOARD OF COMMISSIONERS ETHNIC, FAMILY OWNERSHIP AND THE AGE OF THE COMPANY TOWARDS THE PERFORMANCE OF THE COMPANY LQ45 COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Putra, Ramdani Bayu; Yeni, Fitri; Fitri, Hasmaynelis; Melta, Diki Jasrizal (ADI Journal on Recent Innovation, 2020)
This study aims to examine how the ethnic influence of the board of commissioners (Chinese) on company performance, family ownership of company performance and company age on company performance. And the effect of all independent variables on dependent. The population of this study is the LQ45 company listed on the Indonesia Stock Exchange from 2013-2017. The sampling technique in this study is Purposive Sampling. Based on observations from 2013-2017 the samples in this study were 23 companies from the LQ45 company. This study uses panel data and the method used is the Hausman Test using Random Effect Model. The results of this study indicate that the Ethnic Board of Commissioners and family ownership do not affect the Company Performance while the Company Age has a positive effect on Company Performance. Taken together,it turns out that Ethnic Board of Commissioners, Family and Company Ownership have a negative influence on the Company's Performance in LQ45 Companies that are listed on the Indonesia Stock Exchange in 2013-2017. Finally, the authors suggest that the performance of the company increases the company must increase the Age of the Company by continuing to carry out or run company activities so that they have more experience and the authors also suggest that further research add variable size companies to get better research results.